Effects of regulatory B cells on intracranial aneurysms by mediating IL-1β/IL-1R pathways: Regulatory B-cells’ role in intracranial aneurysms - Shi, Chanhong; Tian, Fang; Yang, Xuewei; Song, Jinhui; Qi, Dongwang; Li, Jianwei (Cellular and Molecular Biology, 2024)
The purpose of this study was to explore the effects of regulatory B-cells (Breg) on intracranial aneurysms by mediating IL-1β/IL-1R pathways. The study involved 60 patients undergoing angiography in a hospital from January to June 2022, divided into two groups: 30 with intracranial aneurysms (observation group) and 30 without (control group). Researchers extracted peripheral blood mononuclear cells (PBMC) to analyze the proportion of CD19+CD24hiCD38hiB cells using flow cytometry. These cells, along with T-cells and regulatory T-cells (Treg), were isolated through magnetic bead cell sorting. Following co-culture, the proliferation of T-cells and their related secretory factors were assessed. Additionally, Breg cells, treated with an IL-1R receptor blocker or IL-1R expression adenovirus, were studied to evaluate the levels of IL-10 and TGF-β. In the study, the observation group showed lower levels of CD19+CD24hiCD38hiB cells, IL-10, and TGF-β in PBMC than the control group (P<0.05). T-cell proportions were similar in both groups pre and post co-culture (P>0.05). Post co-culture, IFN-γ decreased while IL-4 increased in both groups. The observation group had higher IFN-γ and lower IL-4 than the control group (P<0.05). TNF-α in CD8+T cells, and granzyme B and perforin mRNA levels decreased post co-culture but were higher in the observation group (P<0.05). IL-10 and TGF-β in Treg cells increased in both groups post co-culture but were lower in the observation group (P<0.05). The observation group also had fewer CD19+IL-1R+IL-10+B cells (P<0.05). After IL-1R blocker addition, IL-10 and TGF-β in the supernatant decreased in the observation group (P<0.05). Following transfection, IL-1 and TGF-β levels increased compared to the blank group (P<0.05). The function of peripheral blood CD19+CD24hiCD38hiB cells is impaired in patients with intracranial aneurysms, which may be related to IL-1β/IL-1R pathways disorder.